HUBUNGAN ANTARA PENGGUNAAN VARIASI METODE MENGAJAR GURU SOSIOLOGI DENGAN MINAT BELAJAR SISWA DI KELAS X SMA PGRI 1 PONTIANAK - Juliandri Syahran; Yohanes Bahari; Amrazi Zakso (Universitas Tanjungpura, 2020)
AbstractThis research is to find out the relationship between variations of teaching and teaching with the interest in learning of class X students of SMA PGRI 1 Pontianak in East Pontianak District, Pontianak City. This research is a type of correlational research. The population in this study were all grade X students of SMA PGRI 1 Pontianak in East Pontianak District, Pontianak City, totaling 78 students. Samples were taken as much as 1 class of the total population with Purposive Sampling techniques, obtained by 39 students. Data obtained by the questionnaire method as the main data collector. Observation, as supporting data. Data were analyzed by descriptive analysis and hypothesis testing.The results showed that the variation of teaching methods included in the category quite varied with the acquisition of an average score of 28.82. Learning interest is included in the high category with the acquisition of an average score of 20.03. Hypothesis test results obtained that the coefficient R2 of 0.164 has an F-test value = 7.243 which is greater than 0.05 This means that the research hypothesis which states: